Code-Mixing in Maia Aleldul TV Podcast: A Sociolinguistic Study - Julianti, Ulfah; Suhartini, Diah; Octaviyani, Aulya; Sari, Lili Nurindah; Sagita, Apriliani; Atiyah, Siti (Jurnal Multidisiplin Sahombu, 2025)
This study examines the phenomenon of code-mixing in the Maia Aleldul podcast, specifically in an episode featuring personal and emotional narratives from the interviewee. The objective of this research is to identify the forms and types of code-mixing that emerge and to analyze the sociolinguistic factors underlying them. The method employed is descriptive qualitative, utilizing listening and note-taking techniques on oral transcript data. The findings indicate that outer code-mixing between Indonesian and English predominates, with code-mixing occurring in the form of words and phrases. The contributing factors include emotional expression, communication style adjustment, bilingual identity, and the influence of digital media. These findings enhance the understanding of linguistic dynamics among urban digital natives.